The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33899/rjs.2021.167680
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Epidemiology of Leishmaniasis in Iraq

Abstract: Leishmaniasis continues to be a significant public health issue and socioeconomic obstacle in Iraq. The various species of leishmania are transmitted by the bite of sandflies belonging to genus phlebtomus, where high temperatures might prolong the breeding season for this fly species. The current review proved that the infection in the southern regions of Iraq is more than in the northern regions. The incidence of leishmaniasis has increased and expanded to most Iraqi governorates, the reason may be due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The higher cases were males (42) patients, while females were represented (31) of patients. Males and females shared a similar frequency in the age groups without significant differences between them, they were 31(42.47%), 9 (12.33%) and 26 (35.61%), 4 (5.48%) in age groups(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and (15-50) of males and females respectively, as shown in the Table2. Statistical analysis proved that there were no significant (P ≤ 0.01) differences between genders of the studied groups.Table2:…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The higher cases were males (42) patients, while females were represented (31) of patients. Males and females shared a similar frequency in the age groups without significant differences between them, they were 31(42.47%), 9 (12.33%) and 26 (35.61%), 4 (5.48%) in age groups(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and (15-50) of males and females respectively, as shown in the Table2. Statistical analysis proved that there were no significant (P ≤ 0.01) differences between genders of the studied groups.Table2:…”
mentioning
confidence: 72%
“…The second one is the vertebrate host (human), who has an intracellular, non-motile or non-flagellated form called amastigote stage which invade the macrophages of the vertebrate host [4]. World Health Organization (WHO) considers leishmaniasis as one of the nine most important infectious tropical and subtropical diseases that occurring in all continents [5]. Leishmaniasis regards one of the worldwide disease affecting more than 89 countries including: Asia, Africa, southern Europe (old world), and Latin America (new world), paritcularly those countries that suffer from poverty in social and economic conditions.…”
mentioning
confidence: 99%
“…CL cases are widespread in most Iraqi provinces, and the first patients affected were reported in the cities of Mosul and Baghdad [18]. Previously, medical education and health care in Iraq were the most developed in the area [19].…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained in 1996 survey CDC of Salmonella isolates revealed that 37% were resistant to at least one antimicrobial agent (6,9). Local study in 1993 reported that all S.typhimurium, S.wien, S.muencher, S.senftenberg and S.enek have resistance range from 11%-66% to chloramphenicol, ampicillin, streptomycin, tetracycline, and gentamycin (10). Other hocal studies revealed some identical antibiotic resistance patterns among Salmonella, Shigella, and ‫مجلة‬ ‫كلية‬ ‫التربية‬ ‫األساسية‬ ‫ملحق‬ ‫العدد‬ ‫السادس‬ ‫والسبعون‬ 2102 2 E.coli, with inclusive resistance to ampicillin penicillin G and tetracycline (11,12).…”
Section: Introductionmentioning
confidence: 99%

Plasmid content studies of local isolates of Salmonella

Ass, Prof. Dr. Israa Abdul Jabbar Ibrahim,
Prof. Dr. Amur Al Najar,
Prof. Dr. Muhammad Abdul Kaddar
2023
cbej